PENGARUH SOCIAL MEDIA USAGE, PEER INFLUENCE TERHADAP KEPUTUSAN PEMBELIAN MELALUI ELECTRONIC WORD OF MOUTH SEBAGAI VARIABEL INTERVENING PADA ONLINE MARKETPLACE - Muhammad Naufal Rafi Hendarman; Meta Andriani (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to examine the influence of social media, peer influence on purchasing decisions through electronic word of mouth as an intervening variable in online marketplaces. Primary data collection is carried out for 1 week. This study used a research sample that had met the criteria of 100 respondents. This study used a descriptive research design approach with empirical data collected through online surveys. Empirical data is then processed using the Structural Equation Modeling approach to test a number of hypotheses proposed. The results of this study Social Media Usage have a positive effect on Electronic Word of Mouth. Peer Influence positively influences Electronic Word of Mouth. Social Media Usage has a positive effect on Purchase Decision. Peer Influence has no effect on Purchase Decisions. Electronic Word of Mouth has no effect on Purchase Decision. Social Media Usage does not affect Purchase Decisions through Electronic Word of Mouth. Peer Influence does not affect Purchase Decisions through Electronic Word of Mouth.